2009
DOI: 10.1103/physrevc.80.031304
|View full text |Cite
|
Sign up to set email alerts
|

Shape evolution in self-conjugate nuclei, and the transitional nucleusSe68

Abstract: We report on the first measurement of the absolute transition strength B(E2; 0 + 1 → 2 + 1 ) in the self-conjugate nucleus 68 Se. It is found that the 0 + 1 → 2 + 1 transition displays a strength similar to that for the triaxial 64 Ge nucleus, in sharp contrast to the much stronger collectivity observed for the oblate 72 Kr nucleus. Shape evolution along the N = Z line from zinc to strontium is analyzed through beyond-mean-field calculations using the D1S force. Over this narrow mass region the nuclear structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
35
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 28 publications
5
35
0
Order By: Relevance
“…It has been shown that the ground states of the even-even 74−82 Se are prolate-deformed [21,22]. However, for the lighter 68,70,72 Se isotopes, there is evidence for oblatedeformed ground states [23][24][25], but this has been called into question by other studies [26,27]. Theoretically, a number of microscopic approaches support an oblate ground-state shape that evolves rapidly into a prolate collective rotation for spin J 6 [24,[28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 53%
“…It has been shown that the ground states of the even-even 74−82 Se are prolate-deformed [21,22]. However, for the lighter 68,70,72 Se isotopes, there is evidence for oblatedeformed ground states [23][24][25], but this has been called into question by other studies [26,27]. Theoretically, a number of microscopic approaches support an oblate ground-state shape that evolves rapidly into a prolate collective rotation for spin J 6 [24,[28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 53%
“…The need for fairly high effective charges of e p ≈ 2 illustrates the importance of core excitations across the N = 50 shell gap which are outside of the employed model space. The experimental data stems from the present work and references [6,7,17,33,35,36]. …”
Section: A Intermediate-energy Coulomb Excitationmentioning
confidence: 99%
“…Their properties are driven by shape coexistence and rapid shape changes all the way from the N = Z line into the A ≈ 70 mass region [1][2][3][4][5][6][7][8][9][10][11][12][13]. On the other side of the nuclear chart, the most neutron-rich selenium and germanium isotopes accessible for experiments are around the magic neutron number N = 50.…”
Section: Introductionmentioning
confidence: 99%
“…This restriction is one of the major drawbacks of the method because it limits its applicability to systems where triaxiality does not play an important role. However, many exciting experimental and theoretical phenomena are closely related to the triaxial degree of freedom, for instance: the presence of γ-bands in the low lying energy spectra and γ-softness, shape coexistence and shape transitions in transitional regions [13,[15][16][17][18][19][20]; the lowering of fission barriers along the triaxial path [21][22][23]; the influence of triaxial deformation in the ground state for the mass models [24,25]; triaxiality at high spin [26][27][28]; the observation of K-bands and isomeric states in the Os region [29][30][31]; or some other exotic excitation modes such as wobbling motion and chiral bands [32][33][34].…”
Section: Introductionmentioning
confidence: 99%